Diretrizes para o gerenciamento da água pluvial nas edificações escolares municipais da cidade de Ribeirão Preto - Hernandes, André Teixeira (Universidade Federal de São Carlos, 2006)
The current projects of rainwater plumbing systems are extremely simple and present only one exclusive concern: to divert the rainfall from the place where it occurs to the drainage public system. In general, it s possible to verify that they do not attend even the word semantic meaning. The no existence of a coordinated set of action aiming at ampler results makes rainwater plumbing system unconcerned with the surrounding area, not composing harmonically with the urban site in particular, and the environment as a general form. Generally, designers expect only rainwater goes toward out of the site, and that is a good result of a good system. Due the lack of attention to the impact that generates and does harm to society, they ignore its potential as instrument of water building conservation. They do not assess correctly its capacity as a source of supply of so expensive and scarce water, according with its necessities, conveniences or limitations that can exist. Therefore, the goal of this study is to propose a new function for the rainwater plumbing system, in special for Ribeirão Preto municipal school buildings, becoming it from a passive to an active system of environment protection. With a proper and molded conception for this new proposal, the system must contemplate the aspects related to the reduction of the impacts caused by the civil construction activities on urban sites, its preservation and providing environment education for people and also, as an worthy water building management tool.
Guidelines on rainwater management for Ribeirão Preto municipal school buildings
Keywords: Águas pluviais; Água - conservação; Aproveitamento de água pluvial; Sistemas prediais; Stormwater management; Rainwater plumbing systems; Water conservation; Rainwater harvesting; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL